The Educational and Language Policy Demands of the Indigenous Peoples of Chile: A View from the Perspective of Linguistic Rights - Loncon-Antileo, E (Springer International Publishing, 2023)
In 1994, (Chiodi and Loncón, Crear nuevas palabras. Innovación y expansión de los recursos lexicales del mapuzugun, Universidad de la Frontera y Corporación Nacional de Desarrollo Indígena, 1999) warned about the chronic inequality between Spanish and Mapudungun, as well as the consequences for the Mapuche language due to the superiority of Spanish, identifying the following problems: (a) perpetuation in orality in a context of generalized literacy, (b) paucity of intellectualization and lack of formal records in the knowledge of modern and universal culture, (c) lexical impoverishment, (d) linguistic acculturation, (e) substitution and displacement, (f) danger of dialectal fragmentation, and (g) lack of social prestige and weakening of linguistic loyalty. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.